2019
DOI: 10.2147/tcrm.s184291
|View full text |Cite
|
Sign up to set email alerts
|

<p>Idiopathic pulmonary fibrosis and GERD: links and risks</p>

Abstract: Gastroesophageal reflux disease (GERD) and idiopathic pulmonary fibrosis (IPF) are two pathological conditions often strictly related, even if a clear relationship of causality has not been demonstrated. GERD is a frequent comorbidity in IPF patients, as demonstrated using combined multichannel intraluminal impedance-pH, despite being mostly clinically silent. According to that, it has been hypothesized that microaspiration of gastric material may play a fundamental role in the fibrotic transformation of pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 86 publications
(136 reference statements)
0
44
0
Order By: Relevance
“…However, this recommendation carries very low confidence in effect estimates. On the contrary, recent studies not only question the relevance of the above mention retrospective findings but also associate the use of PPI with an increased risk of lung infections and a negative prognostic outcome [15]. Therefore, AAT prospective randomized trials in IPF are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this recommendation carries very low confidence in effect estimates. On the contrary, recent studies not only question the relevance of the above mention retrospective findings but also associate the use of PPI with an increased risk of lung infections and a negative prognostic outcome [15]. Therefore, AAT prospective randomized trials in IPF are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…PPI are used in the case of symptomatic GERD by 44% of the respondents and 12% use PPI regardless of GERD symptoms (43% and 11% in the previous survey, respectively). Although the potential role of gastroesophageal reflux (GER) in IPF pathogenesis and progression is not fully explained, it is suggested that AAT may decrease the risk for microaspiration-associated lung injury or damage, a mechanism that has been postulated to cause or worsen IPF [15]. Based on the encouraging retrospective clinical data, that PPI can stabilize lung function and reduce disease flares and hospitalizations, the international treatment guidelines recommend the use of AAT in IPF with the treatment indication being IPF and not GERD [4].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, the burden of proof is most substantial for GERD associated with IPF [67]. Chronic microaspiration insults may lead to pulmonary parenchyma damage attracting persistent inflammation resulting in fibrotic remodeling [68,69]. Tracheal pepsin is a predictable indicator of aspiration [70].…”
Section: Gerd (Gastroesophageal Reflux Disease)mentioning
confidence: 99%
“…In a post-hoc data evaluation of the INPULSIS trials, IPF acute exacerbations frequently occurred on antacid therapy than those not on it [81]. PPI use results in alkaline gastric pH, which loses its bactericidal effect and increases respiratory infections on aspiration [69]. The clinical data available does not agree with a GERD and IPF relationship [82].…”
Section: Gerd (Gastroesophageal Reflux Disease)mentioning
confidence: 99%
See 1 more Smart Citation